(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
Between the late nineteenth century and the World War I, several factors pushed secular and Catholic educational agencies to theorize pedagogical lines specifically aimed at governing individual sexuality. In the Catholic sphere, the pedagogical proposal hinged on an almost complete, even terminological, removal of sex and sexuality: that dimension of human life was veiled and compressed within a bipolar linguistic horizon: at one extreme “purity”, at the other “instincts”, “passions” and “senses”. The construction phase of this pedagogical model – which in its various transformations was central at least until the 1960s – coincided in practice with the first diffusion of cinema, going on to profoundly influence the Catholic approach to the new medium: in the atlas of Catholic pedagogy, cinema was immediately catalogued among the most resolute opponents of the “angelic virtue” of “purity”. This contribution intends to propose a long-term analysis aimed at highlighting the evolution of the relationship between this pedagogical model and film policy in Catholicism, identifying the links between this relationship and the progressive sexualization of Italian cinema.